Transcriptional regulation of ZIP genes is independent of local zinc status in Brachypodium shoots upon zinc deficiency and resupply. (29th July 2021) - Amini, Sahand; Arsova, Borjana; Gobert, Sylvie; Carnol, Monique; Bosman, Bernard; Motte, Patrick; Watt, Michelle; Hanikenne, Marc
Abstract: The biological processes underlying zinc homeostasis are targets for genetic improvement of crops to counter human malnutrition. Detailed phenotyping, ionomic, RNA‐Seq analyses and flux measurements with 67 Zn isotope revealed whole‐plant molecular events underlying zinc homeostasis upon varying zinc supply and during zinc resupply to starved Brachypodium distachyon (Brachypodium) plants. Although both zinc deficiency and excess hindered Brachypodium growth, accumulation of biomass and micronutrients into roots and shoots differed depending on zinc supply. The zinc resupply dynamics involved 1, 893 zinc‐responsive genes. Multiple zinc‐regulated transporter and iron‐regulated transporter (IRT)‐like protein (ZIP) transporter genes and dozens of other genes were rapidly and transiently down‐regulated in early stages of zinc resupply, suggesting a transient zinc shock, sensed locally in roots. Notably, genes with identical regulation were observed in shoots without zinc accumulation, pointing to root‐to‐shoot signals mediating whole‐plant responses to zinc resupply. Molecular events uncovered in the grass model Brachypodium are useful for the improvement of staple monocots. Abstract : Zinc resupply to zinc‐starved plants triggers a highly dynamic transcriptional response in the model grass Brachypodium. Within 10 min occurs a transient zinc shock response in roots that is signalled to shoot tissues.